Analysis on Light Extraction Efficiency of Aluminum Gallium Nitride-Based Ultraviolet-C Light Emitting Diode with Patterned Surface in FDTD - Htwe Ei Ei Khin; Hla, Tin Tin (AI Society & STMIK Indonesia, 2025)
This paper presents the analysis on light extraction efficiency (LEE) of each polarization mode for Aluminum Gallium Nitride (AlGaN)-based Ultraviolet-C (UV-C) light emitting diodes(LEDs) with patterned substrate surfaces. LEE is severely constrained by the substantial refractive index contrast and polarization-dependent losses, especially transverse magnetic (TM) mode polarized light that predominates at shorter wavelengths. This study employs two dimension (2D) Finite-Difference Time-Domain (FDTD) simulations to investigate the effects of flat, equal triangular patterned, and isosceles triangular patterned surfaces on the LEE of both transverse electric (TE) and transverse magnetic (TM) modes in order to solve this issue. The specific objective of this study is to evaluate the maximum light extraction efficiency for each polarization mode of AlGaN-based UV-C LED with flat surface and patterned surfaces. Simulation results show that the patterned surfaces have better performance than flat surface. This study concludes that isosceles triangular patterning is the most effective approach for maximizing light extraction efficiency compared with equal triangular patterning and flat surfaces in AlGaN-based UV-C LEDs, providing a pathway toward the development of high-efficiency deep UV emitters.